2013
DOI: 10.1016/j.fuproc.2011.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Ash transformations in pulverised fuel co-combustion of straw and woody biomass

Abstract: Ash transformation processes have been studied during co-firing of wheat straw and pine stem wood and softwood bark. Pilot-scale trials in a 150 kW pulverised-fuel-fired burner were performed. Thermodynamic equilibrium calculations were made to support the interpretation of the results. The results show that fast reactions involving gaseous ash compounds are favored at the expense of reactions where condensed components participate. Accordingly, the conditions promote gas phase reactions resulting in the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 14 publications
2
76
0
Order By: Relevance
“…Previous studies have reported high particulate emissions and increased slagging tendencies of straw pellets, even with improved air staging in domestic appliances ( € Orberg et al 2014;Kortelainen et al 2015), which has limited their use to mainly medium-and large-scale combustion systems (Nordgren et al 2013). When the toxicity of the emissions was evaluated, we found that straw pellet combustion induced the most pronounced inflammatory effects of the pellet fuels, but otherwise the responses were on a similar level to the emissions from the Miscanthus sp.…”
Section: Wheat Straw Pelletsmentioning
confidence: 57%
“…Previous studies have reported high particulate emissions and increased slagging tendencies of straw pellets, even with improved air staging in domestic appliances ( € Orberg et al 2014;Kortelainen et al 2015), which has limited their use to mainly medium-and large-scale combustion systems (Nordgren et al 2013). When the toxicity of the emissions was evaluated, we found that straw pellet combustion induced the most pronounced inflammatory effects of the pellet fuels, but otherwise the responses were on a similar level to the emissions from the Miscanthus sp.…”
Section: Wheat Straw Pelletsmentioning
confidence: 57%
“…Possibly, it might be beneficial to subject a wood-based fuel to pyrolysis prior to combustion. The advantages of wood-based fuels compared with coal are lower CO 2 emissions and a lower ash content (Nordgren, 2013). The use of waste material as an energy supply is required in cement production to make it economically possible, and burners are developed for this (Vaccaro, 2006).…”
Section: Outlook For the Grate-kiln Processmentioning
confidence: 99%
“…Biomass resources are favored because they are clean, renewable, contain low levels of nitrogen, and can effectively address the pollution and global warming problems presented by traditional energy sources (Ma et al 2008;Khan et al 2009;Qin et al 2010;Kirtay 2011). Biomass gasification technology is an advanced means of biomass energy conversion; however, the high alkali metals content in straw wastes, such as corn straw and rice straw, can accumulate in the ash on gasifier heating surfaces, from slag-bounding in a furnace, and from agglomeration of bed material and similar technologies Niu et al 2010;Nordgren et al 2013) because of the sticky deposition layer of sodium and potassium (Doshi et al 2009). Therefore, it is essential to study the migration and conversion of alkali metals during biomass gasification.…”
Section: Introductionmentioning
confidence: 99%